Structure and processing issues of thin film nonlinear optical polymers: Design of tougher NLO polymers using chain parameters - Song, K; Kim, N (GORDON BREACH SCI PUBL LTD, 1996)
One of critical problems in the preparation of electro-optic devices from NLO polymers is their brittle nature and tendency to form cracks during the device fabrication process. In order to design a new NLO polymer with improved toughness, a computer modeling study has been carried out developing correlations between molecular parameters and toughness of polymers. When polycarbonate instead of PMMA is used as a backbone chain for the NLO polymer, a significant improvement in toughness of NLO polymers are found. This finding suggests an important strategy in designing a new NLO polymer because the cracking problem can be eliminated without sacrificing any other necessary requirements for NLO materials.
Keywords: ENTANGLEMENT